2009
DOI: 10.1093/ndt/gfp297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiovascular risk in paediatric peritoneal dialysis patients: a Turkish Pediatric Peritoneal Dialysis Study Group (TUPEPD) report

Abstract: Elevated levels of atherosclerotic/ inflammatory risk factors, low haemoglobin levels and loss of residual renal function and their negative effects on heart are of remarkable importance in paediatric patients on maintenance peritoneal dialysis. Achieving recommended targets for haemoglobin, blood pressure and Kt/V urea, preserving residual renal function as well as managing inflammation and subsequent arteriosclerosis is obviously essential to improve the patients' prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 58 publications
3
43
0
1
Order By: Relevance
“…25,30,31 The prevalence of LVH in predialysis pediatric patients has been varied between 7% and 39% in different studies 3,6,9,10 and anemia, hypertension, age, increased cardiac output, elevated PTH levels have been reported as independent predictors of LVH. 3,18,19,32,33 In our study, we determined that LVH was more frequent than those found in previous studies, with a prevalence of 44%, and as expected, tended to be higher in severe CRI. LVMI correlated negatively with Hb level, age, height, while positively with E/E 0 ratio.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…25,30,31 The prevalence of LVH in predialysis pediatric patients has been varied between 7% and 39% in different studies 3,6,9,10 and anemia, hypertension, age, increased cardiac output, elevated PTH levels have been reported as independent predictors of LVH. 3,18,19,32,33 In our study, we determined that LVH was more frequent than those found in previous studies, with a prevalence of 44%, and as expected, tended to be higher in severe CRI. LVMI correlated negatively with Hb level, age, height, while positively with E/E 0 ratio.…”
Section: Discussionsupporting
confidence: 79%
“…In previous studies, reduced E/A ratios in children on dialysis have often been reported. 7,8,18,19 In addition, Mitsnefes et al 6 determined low E/A ratios in predialysis pediatric patients as well. Whereas, in another studies in CKD patients, E/A ratios were similar to that in healthy children, in contrast to Mitsnefes et al 9, 10 We also did not find any significant difference in E/A ratios between the patient and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The association between cIMT and MAP, as well as highsensitivity C-reactive protein in peritoneal dialyzed children has been reported. In this group of patients cIMT correlated negatively with hemoglobulin and albumin levels, and with Kt/V urea [16].…”
Section: Atherosclerosis and Vascular Stiffnessmentioning
confidence: 63%
“…Associated factors include hypertension, body mass index, type of peritoneal dialysis applied, anemia and hyperparathyroidism, as well as the etiology of CKD other than renal dysplasia 8,14,15 .…”
Section: Discussionmentioning
confidence: 99%